Can Land Rregistration and Certification Reduce Land Border Conflicts? - Stein T. Holden; Klaus Deininger; Hosaena Ghebru (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2011)
This paper assesses factors related to local land border conflicts and how lowcost land registration and certification has affected land conflicts during and after land registration and certification using data from northern Ethiopia. Border conflicts were more common near district centers, further away from markets, and where property rights had been redistributed more recently. A higher probability of reduction in conflicts during and after the reform was positively associated with nearness to markets, longer distance to district centers, more recent land redistribution, better quality border demarcation and plot measurement during registration, and less involvement by local elders in adjudication
Keywords: Q15; 330; Land registration and certification; low-cost land reform; impact on land disputes; land border disputes; conflict mediators; Ethiopia